2021
DOI: 10.1111/ddi.13241
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of genus‐level phylogenetic endemism in the tree flora of Mediterranean Europe

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 92 publications
1
10
0
Order By: Relevance
“…The only available large‐scale, dated phylogeny was produced very recently and was done at the genus level (Cheikh Albassatneh et al . 2021). And the first species dataset of traits and occurrences has only recently been assembled (Monnet et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only available large‐scale, dated phylogeny was produced very recently and was done at the genus level (Cheikh Albassatneh et al . 2021). And the first species dataset of traits and occurrences has only recently been assembled (Monnet et al .…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, comprehensive phylogenetic and functional trait datasets are scarce for Mediterranean tree species. The only available large-scale, dated phylogeny was produced very recently and was done at the genus level (Cheikh Albassatneh et al 2021). And the first species dataset of traits and occurrences has only recently been assembled (Monnet et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The first large‐scale spatial phylogenetic analyses began to appear in 2014, initially focused on Australia because herbarium digitization reached a critical mass there first (González‐Orozco et al, 2015, 2016; Mishler et al, 2014; Nagalingum et al, 2015; Schmidt‐Lebuhn et al, 2015; Thornhill et al, 2016). Later studies expanded around the world to New Zealand (Heenan et al, 2017), California (Thornhill et al, 2017), Chile (Scherson et al, 2017), the Pacific Northwest (Link‐Pérez & Laffan, 2018), Mexico (Sosa et al, 2018), Wisconsin (Spalink et al, 2018), Florida (Allen et al, 2019), conifers of the world (Mekala et al, 2019), Norway (Mienna et al, 2020), Africa (Dagallier et al, 2020), Mediterranean Europe (Cheikh Albassatneh et al, 2021), Italy (Bartoli et al, 2021), Greece (Kougioumoutzis et al, 2020, 2021), all of North America (Carter et al, 2022; Mishler et al, 2020), China (Zhang et al, 2021, 2022; Zhu et al, 2021) and Japan (Nitta et al, 2022).…”
Section: Historymentioning
confidence: 99%
“…Tree flora have been shown to be important biodiversity surrogates for highly heterogeneous areas (Latini et al 2017), like Algeria. A recent study indicated that some Mediterranean areas contain a disproportionately high phylogenetic diversity with a concentration of palaeo-endemic species (Cheikh Albassatneh et al 2021). Hence, a focus on tree species constitutes a key issue to assess floristic diversity and develop proper conservation strategies (Médail et al 2019).…”
Section: Introductionmentioning
confidence: 99%